2017
DOI: 10.3389/fpsyg.2017.01904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phonological Training on the Reading and Reading-Related Abilities of Hong Kong Children with Dyslexia

Abstract: This study aimed to investigate phonological awareness training by examining outcomes among Chinese children who learn Chinese without phonetic system training. Fifty-six Hong Kong children from the 3rd to 6th grades were recruited. Two-thirds of the children had been officially identified as dyslexic by the local government, and the remainder were considered high risk for dyslexia. The children were divided equally into a control group and an experimental group, with the groups matched as closely as possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 75 publications
(91 reference statements)
2
8
0
1
Order By: Relevance
“…In this subgroup, the test-retest correlation drops to r = .77. Unsurprisingly, two recent randomized controlled trials, reviewed in Study 1, reported the test-retest correlation (Wang, 2017;Wang, Liu, & Xu, 2019), and specified that this measure was .94 according to the test battery, but only .81 and .78, respectively, when calculated in their own samples of children with dyslexia. In addition, Cirino et al (2002) reported that the test-retest correlation among standard scores from major reading batteries ranged between .46 and .92, with a median of about .70, in a sample of 78 children with reading disability.…”
Section: Introductionmentioning
confidence: 99%
“…In this subgroup, the test-retest correlation drops to r = .77. Unsurprisingly, two recent randomized controlled trials, reviewed in Study 1, reported the test-retest correlation (Wang, 2017;Wang, Liu, & Xu, 2019), and specified that this measure was .94 according to the test battery, but only .81 and .78, respectively, when calculated in their own samples of children with dyslexia. In addition, Cirino et al (2002) reported that the test-retest correlation among standard scores from major reading batteries ranged between .46 and .92, with a median of about .70, in a sample of 78 children with reading disability.…”
Section: Introductionmentioning
confidence: 99%
“…phonemic processes as phonemic perception, phonemic analysis and phonemic synthesis, without which it is impossible to acquire the syllabic structure of a word and literacy. (Wang & Li-Chih, 2017). All this indicates that the level of the articulation and phonological aspect of speech has a direct impact on a child's performance in primary school in Russian and reading classes, as well as in other subjects, since welldeveloped articulation and phonological aspect of speech is the first step on the way to becoming literate, acting as a scaffold for the whole process of learning to read and write.…”
Section: Violation Of Phonemic Hearing and Perception Prevent Normal mentioning
confidence: 99%
“…Phonological awareness has been shown to be the basis of success in reading, by increasing phonological awareness will improve reading skills. (Dai et al, 2016;Layes et al, 2020;Mather & Wendling, 2012;Peters et al, 2019;Pfost et al, 2019;Snellings et al, 2009;Wang, 2017). Therefore, it is very important for dyslexic students to get special instruction in phonological awareness because this teaching has an impact on reading ability (Berninger & Wolf, 2009).…”
Section: Introductionmentioning
confidence: 99%